Penerapan Model Rational Unified Process (RUP) Dalam Membangun Aplikasi Promosi dan Penjualan Berbasis Web (Studi Kasus: Toko Mie Ayam â€œNeng Kene Kiyehâ€) - Chandra, Yudi Irawan; Irawati, Diyah Ruri; Riastuti, Marti (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
This research discusses the application of the Rational Unified Process (RUP) Model in the development of web-based promotion and sales applications, with a case study at the Chicken Noodle Shop â€œNeng Kene Kiyehâ€. The purpose of this research is to design and implement applications that can increase the efficiency of promotion and sales of chicken noodle products through digital platforms. The RUP method was chosen because of its iterative approach and focus on user needs, allowing for more structured and controlled software development. The RUP model consists of four main phases: inception, elaboration, construction, and transition. In the inception phase, a needs identification and feasibility study are conducted to ensure that the application to be developed matches the business needs of the store. The elaboration phase involves more in-depth analysis and system design, including use case modeling, risk analysis, and application architecture design. In the construction phase, application development is carried out with an iterative approach, allowing for improvements and adjustments based on user feedback. The transition phase involves application testing and end-user training, as well as full system implementation. The result of this research is a web application that has main features such as product catalog, online ordering system, inventory management, and integrated digital promotion. The implementation of this application is expected to increase the visibility of Chicken Noodle Shop â€œNeng Kene Kiyehâ€ in the digital market, simplify the ordering process for customers, and increase sales. The trial shows that this application can function as expected, and provides significant benefits in the store’s operational processes. The conclusion of this research is that the application of the RUP model can be an effective approach in building web-based promotional and sales applications, with a focus on meeting user needs and improving business performance.